In liberal doses - Marina Mahathir (Archipelago Press ; Star Publications (Malaysia), 1997)
Marina's "Musings" columns for The Star newspaper -- compassionate, outspoken, liberated, and unabashedly liberal -- are a talking point in Malaysia's capital and throughout the country. They began as a regular personal commentary on Marina's everyday life as a mother, hut as time went on the range expanded. Her writing came to touch on, and often debate, vital issues of national and global importance and are eagerly read by a huge public. This book collects the best of the columns since 1991, and Marina herself introduces the pieces, putting them into perspective -- a perspective quite different than what is typically reported in the Western media. - See more at: http://www.betterworldbooks.com/in-liberal-doses-id-9839950770.aspx&utm_source=Affiliate&utm_campaign=Text&utm_medium=booklink&utm_term=3630151&utm_content=Homepage#sthash.gVCQETuk.dpuf